Individual monitoring of internal and external contamination in diagnostic or therapeutic use of radionuclides in medicine. (September 2016) - Sarti, G.; Busca, F.; Del Dottore, F.; Sanniti, S.
Abstract : Introduction: Monitoring of internal exposure and external contamination for nuclear medicine workers requires frequent measurements due to the short physical half- lives of most radionuclides used in this field. Purpose: The aim of this study was to develop screening procedures performed at the workplace by local staff using standard laboratory equipment to detect whether potential intake has occurred following ISO/DIS 16637, draft 2014 "Monitoring and internal dosimetry for staff exposed to medical radionuclides as unsealed sources" Material and method: Daily measurements of the ambient dose rate with scintillation detector and surface contamination monitor in front of the abdomen, thyroid and hands to detect whether potential intake or superficial contamination has occurred. Results: For radionuclides with very short physical half-lives such as 99mTc and 18, screening procedures consist in performing daily measurements of the ambient dose rate in front of the abdomen. For pure beta emitters, i.e. 90Y the procedure consists in measuring hand contamination immediately after use. Such measurements (triage monitoring) do not enable to determine the committed effective dose, but are adequate to verify that a given threshold is not exceeded. If the thresholds are exceeded, the survey (special monitoring) is will deepen (for example with in-vitro measurements in escreta samples) Conclusions: Screening measurements for detecting potential radioactivity intake and surface contamination of the hands by nuclear medicine workers enable an acceptable monitoring practical and economic.